IMPLEMENTASI MODEL STAD UNTUK MENINGKATKAN LITERASI BUDAYA SISWA KELAS III DI SD NEGERI 2 PLIKEN - Salma Dwi Amanda; Azis Nurrozikin; Badarudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low interest in reading written information among grade III students. This condition often causes students to experience misunderstandings or misconceptions in understanding the contents of the material, including in the context of learning about cultural diversity. The purpose of this study is to improve students' cultural literacy through the application of the Student Teams Achievement Division (STAD) learning model integrated with the Culturally Responsive Teaching (CRT) approach to the material